1994
DOI: 10.1016/0167-4870(94)90007-8
|View full text |Cite
|
Sign up to set email alerts
|

Scarcity and preference: An experiment on unavailability and product evaluation

Abstract: Scarcity and preferenceVerhallen, T.M.M.; Robben, H. ABSTRACTThe experiment reported examined the effects of four conditions of product availability on consumers' preferences for recipe books, and the corresponding uniqueness judgments and cost evaluations for the same products. These conditions were unlimited availability, limited availability due to popularity, limited availability due to limited supply and accidental unavailability.The results varied according to whether other people's choices depended on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
154
2
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(166 citation statements)
references
References 22 publications
5
154
2
5
Order By: Relevance
“…Furthermore, this desire also increases when the product is also perceived as expensive [44], [106]. Therefore, the more unique a product or service is perceived to be and the more expensive it is compared to usual standards, the more valuable it becomes [106]. In addition, the functional value of uniqueness also strengthens the individual's need to be unique and set himself apart from the social environment within which he or she is embedded [101].…”
Section: Social Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, this desire also increases when the product is also perceived as expensive [44], [106]. Therefore, the more unique a product or service is perceived to be and the more expensive it is compared to usual standards, the more valuable it becomes [106]. In addition, the functional value of uniqueness also strengthens the individual's need to be unique and set himself apart from the social environment within which he or she is embedded [101].…”
Section: Social Characteristicsmentioning
confidence: 99%
“…Furthermore, this desire also increases when the product is also perceived as expensive [44], [106]. Therefore, the more unique a product or service is perceived to be and the more expensive it is compared to usual standards, the more valuable it becomes [106].…”
Section: Social Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequently, the use of these cognitively ''cheap'' rules leads to a fast and relatively accurate appraisal of the merits of the appeal: If (e.g.) a product is ''almost out of stock,'' a large number of prior customers may have bought the product based on product merits and opportunities to buy in the future may be rare or high cost [40]. Thus, without engaging in full and cognitively costly processing, a user can make a choice based on an accurate peripheral cue [12].…”
Section: Persuasion Principlesmentioning
confidence: 99%
“…The customer will often interpret the quantity limitation as a signal for a top-quality or high-value product (Lynn, 1992), or as a signal for an attractive deal (Inman, Peter and Raghubir, 1997), which results in increased consumption. Previous empirical studies found that while such limitations lead to more frequent or greater volume purchases (Inman, Peter andRaghubir, 1997, andVerhallen andRobben, 1994), choices are affected by the extent of the limitation. Wansink, Kent and Hoch (1998) demonstrated that customer motivation for increased consumption is dependent on limitation size -low limitation ("up to 4 products") is a strong indication for customers that the deal is worthwhile, while high limitation ("up to 12 products") is a weaker signal, but it performs as an anchor that can significantly divert customer decisions, as it suggests to customers what may be viewed as reasonable consumption.…”
mentioning
confidence: 99%